Perancangan Manajemen Pengembangan TI Agile Untuk Transformasi Digital InsurCo Dengan COBIT 2019 DevOps - Muhammad Haikal Qolby; Rahmat Mulyana; Widyatasya Agustika Nurtrisha (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The rapid advancement of Information Technology (IT) has significantly impacted various sectors and presented increasingly complex challenges. Digital Transformation (DT) has become crucial for incumbent companies to survive and remain competitive in this digital era. However, many TD investments have failed, necessitating adequate Information Technology Management Governance (ITMG) for achieving company objectives. Previous research has shown the importance of hybrid traditional ITMG with agile practices. However, the design of agile ITMG needs further refinement as a reference for implementation. InsurCo is a state-owned enterprise that is obligated to implement ITMG based on the PER-2/MBU/03/2023 regulation, as well as accelerate DT in line with the direction of the Master Plan for the Financial Services Sector 2021-2025. The research method used is design science research based on interview data and document triangulation. The prioritization of agile ITMG objectives is based on design factors, COBIT 2019 DevOps Focus Area, and previous ITMG mechanisms for digital transformation. Three selected priority objectives of agile ITMG are DSS05 (Managed Security Services), APO01 (Managed I&T Management Framework), and BAI10 (Managed Configuration), which are evaluated based on seven ITMG components. Recommendations are generated using three aspects: people, process, and technology, with an estimated increase in InsurCo’s ITMG capability of 7.66%. This study contributes to the knowledge